RELIGIOUS MODERATION IN THE PERSPECTIVE OF MAQASHID SHARI'AH AND ITS APPLICATION IN INDONESIA - Ropiah, Siti; Syafi'i, Syafi'i; Haris, Abd (Universitas Islam Madura, 2025)
The purpose of the study is the role of Maqashid Sharia in forming a moderate mindset that respects diversity and maintains a balance between personal and social religious beliefs. In the perspective of Maqashid Sharia, religious moderation does not only include aspects of religious formalities, but refers to the main goal of sharia, namely the benefit of the people. Maqashid Sharia emphasizes five main principles: (hifz al-din), (hifz al-nafs), (hifz al-aql), (hifz al-nasl), and (hifz al-mal). This research uses a qualitative approach with a focus on the analysis of Islamic texts related to the concept of religious moderation. The main data sources of this research consist of classical and modern literature derived from the works of scholars such as Al-Ghazali, Al-Syatibi, and Yusuf Al-Qaradawi. The results obtained in this study are that the concept of religious moderation in Maqashid Syariah provides an overview that Muslims can avoid extremism and intolerance, encouraging the creation of a peaceful and inclusive society. In Indonesia, as a diverse country in terms of religion and culture, the application of religious moderation values from the perspective of Maqashid Syariah is very relevant to strengthen national unity and unity. The implications of this study reinforce the concept of religious moderation as part of Maqashid Shari'ah, which emphasizes balance in religion to maintain the sustainability of a harmonious social life, this research enriches the study of the relationship between moderate Islamic teachings and national values, reinforcing the narrative that Islam and nationality are not two contradictory things.